Stylet (vestigial shell) size in Octopus vulgaris (Cephalopoda) hatchlings used to determine stylet nucleus in adults - Lourenço, Sílvia (2020)
The estimation of age and growth of cephalopod stocks is a key issue for their sustainable management. Recently, several studies have successfully validated the daily deposition of growth rings in the vestigial shell or stylets of several octopus species. Octopus vulgaris eggs were incubated at two different temperatures, 18 and 22ºC, until hatching to determine stylet size at hatching and assess the effect of temperature in the stylet dimensions. The 3-day-old hatchlings were sectioned transversally and 6 mm sections were stained to enhance the stylet position and visibility. The sections were observed under transmitted light microscopy at a magnification of 1000×, and the stylets identified as blue/green structures inside the mantle–funnel retractor muscle. The transversal sections of the whole paralarvae allowed the diameter of the embryonic stylet of an octopus species to be measured for the first time. The mean stylet diameter in 3-day-old paralarvae is 3.99 mm independently of the thermal conditions. Moreover, significant differences in stylet size between captive and wild paralarvae were observed; the latter showed significantly larger stylets, an indication that they are over 3 days old. Our results also indicate that the stylet nucleus is much smaller than previously thought based on measurements in stylets of juveniles and adults.